Skin-sensitive pressure gel bra and preparation method thereof

By using double-end sealed vinyl silicone oil and other components, the skin-feeling pressure-bonded breast patch has solved the shortcomings of existing breast patch products in terms of adhesion, breathability, comfort and plasticity, and has achieved stable fixation and comfortable wearing in different occasions.

CN121136450APending Publication Date: 2025-12-16GUANGDONG QIYUE FUTURE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511346937.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

Existing breast pad products cannot simultaneously achieve multiple advantages such as good adhesion, good breathability, good comfort, good invisibility, and good shaping effect, resulting in a poor user experience in different situations.

Method used

Using double-ended vinyl silicone oil, porous solid filler, hydrophilic silicone oil, hygroscopic agent, foaming agent and other components, a skin-feeling pressure-bonded breast patch is formed through a specific preparation method, which has good adhesion, breathability, comfort and plasticity.

Benefits of technology

It achieves a secure fit against the skin without the need for shoulder straps, is highly breathable, comfortable, and durable, reducing stuffiness and pressure, and enhancing the user's wearing experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005605281620000071
    Figure BDA0005605281620000071
  • Figure BDA0005605281620000081
    Figure BDA0005605281620000081
  • Figure BDA0005605281620000101
    Figure BDA0005605281620000101
Patent Text Reader

Abstract

The invention relates to the technical field of chest paste processing, in particular to a skin pressure sensitive adhesive chest paste and a preparation method thereof.The skin pressure sensitive adhesive chest paste is prepared from, by weight, 30-50 parts of double-terminated vinyl silicone oil, 40-60 parts of porous solid filler, 6-9 parts of hydrophilic silicone oil, 5-10 parts of moisture absorbent, 0.8-1.6 parts of foaming agent, 0.1-0.3 part of platinum catalyst, 2-4 parts of cross-linking agent and 80-100 parts of solvent. The hydrophilic silicone oil is composed of modified amino silicone oil and polyether modified silicone oil according to the weight ratio of 1: (2-4), by adopting the formula, the bra has high viscosity and can be firmly attached to the skin without assistance of shoulder straps, and the problems that a cloth bra is poor in adhesion and prone to slipping off are effectively solved. By adding the porous solid filler, the moisture absorbent and the hydrophilic silicone oil, good air permeability and moisture absorption are provided for the bra, discomfort conditions such as stuffy sweat, pruritus and red swelling of chest skin can be reduced, compared with a silica gel bra, the long-time wearing comfort is greatly improved, and a user can be kept free in various occasions.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of chest pad processing, and more particularly to a skin-feeling pressure adhesive chest pad and a preparation method thereof. BACKGROUND

[0002] A chest pad is a small patch worn on the chest, mainly used to cover the nipples and provide certain support and shaping effects. Currently, chest pads on the market mainly include silicone chest pads and cloth chest pads. Among them, silicone chest pads have strong adhesion and can closely adhere to the skin, so they can be firmly fixed on the chest even without the aid of shoulder straps. Therefore, when wearing clothes that require bare shoulders, such as strapless dresses and formal wear, they can achieve good invisible effects and avoid problems such as shoulder strap exposure. In addition, silicone chest pads also have certain gathering and lifting effects, which can make the chest look fuller and more upright, creating a natural cleavage, thereby visually enhancing the wearer's body curve aesthetics. Moreover, silicone material is relatively durable, and silicone chest pads can generally be washed and reused multiple times, which to some extent improves their cost performance and reduces use costs.

[0003] However, the breathability of silicone material is poor, and when worn for a long time, it can cause chest skin to sweat, leading to skin itching, redness and other discomfort, causing distress to the user. Secondly, silicone chest pads are relatively thick and heavy, and when worn on the chest, they can cause a certain degree of compression, especially after wearing for a long time, the compression will be more obvious, which can affect the user's comfort and normal breathing. Furthermore, with the passage of time, the adhesion of silicone chest pads will gradually decrease, causing the edges to curl, which not only affects the fixing effect of the chest pad, but also can damage the overall aesthetic appearance of the wearer.

[0004] Cloth chest pads have good breathability, allowing the chest skin to remain relatively cool, suitable for long-term wear, reducing skin discomfort caused by sweating, thus providing certain comfort. However, the adhesion of cloth chest pads is relatively weak, and if not assisted by shoulder straps, it is easy to slip off, which greatly limits its use scenarios, such as when wearing some formal occasions like strapless dresses, it is difficult to meet the user's stable fixing needs. Moreover, the material of cloth chest pads is relatively thick, and when worn, it can leave obvious outlines on the surface of the clothes, affecting the invisible effect and making the overall appearance of the wearer look unnatural and smooth.

[0005] It is evident that existing breast petal products on the market, whether made of silicone or fabric, cannot simultaneously offer the advantages of good adhesion, breathability, comfort, invisibility, and shaping. Users often have to choose one type of breast petal product that best suits their specific needs in different situations. This results in a lack of comprehensive and ideal user experience, ultimately reducing the overall comfort and satisfaction of using breast petals. Summary of the Invention

[0006] In order to provide a breast sticker that simultaneously possesses advantages such as good adhesion, good breathability, good comfort, good invisibility, and good plasticity, this application provides a skin-feel adhesive breast sticker and its preparation method.

[0007] In the first aspect, this application provides a skin-feel adhesive breast patch, which adopts the following technical solution: A skin-feel adhesive breast patch is prepared from the following raw materials in parts by weight: 30-50 parts of double-ended vinyl silicone oil 40-60 parts of porous solid filler 6-9 parts of hydrophilic silicone oil 5-10 parts of desiccant 0.8-1.6 parts of foaming agent Platinum catalyst 0.1-0.3 parts 2-4 parts crosslinking agent 80-100 parts of solvent The hydrophilic silicone oil is composed of modified amino silicone oil and polyether modified silicone oil in a weight ratio of 1:(2-4).

[0008] By adopting the above technical solution, the breast patch possesses strong adhesion, allowing it to firmly adhere to the skin without the need for shoulder straps, effectively solving the problems of poor adhesion and easy slippage associated with fabric breast patches. The addition of porous solid fillers, moisture absorbents, and hydrophilic silicone oil provides excellent breathability and moisture absorption, reducing discomfort such as stuffiness, itching, and redness on the chest skin. Compared to silicone breast patches, it significantly improves comfort during extended wear, allowing users to remain comfortable in various situations.

[0009] The use of double-ended vinyl silicone oil and hydrophilic silicone oil gives the breast pads a certain degree of flexibility and resilience. Combined with their good adhesion and breathability, they avoid the discomfort caused by the overly rigid material of some silicone breast pads and can withstand prolonged wear. They also reduce the decrease in adhesion and curling that often occurs with extended use, allowing the breast pads to better conform to the chest and maintain their fixation for longer periods, thus avoiding the problem of diminished fixation that often occurs with silicone breast pads over time.

[0010] The hydrophilic silicone oil is composed of modified amino silicone oil and polyether modified silicone oil. The modified amino silicone oil provides good skin affinity and lubrication, while the polyether modified silicone oil further improves the flexibility and comfort of the breast patch. Simultaneously, the addition of porous solid fillers helps reduce the overall weight of the breast patch, minimizing pressure on the chest and allowing the wearer to maintain a more comfortable experience during extended wear. This addresses the discomfort caused by the bulkiness of traditional silicone breast patches.

[0011] Preferably, the porous solid packing is treated by the following method: 1) Soak the porous solid packing in sodium hydroxide solution for 1-2 hours to activate it, and obtain activated porous solid packing. 2) The activated porous solid packing is added to a benzenesulfonic acid ethanol solution, heated to 50-60℃, and kept heating for 4-6 hours. Then, it is centrifuged, washed, and dried to obtain sulfonated porous solid packing. The concentration of the benzenesulfonic acid ethanol solution is 0.4-0.8 mol / L. 3) Place chitosan in a 0.5-0.8 mol / L acetic acid solution, heat to 70-80℃, and after the chitosan is completely dissolved, add sulfonated porous solid filler, cool to 55-65℃, maintain heating for 1.5-3 hours, filter, take the filter residue, wash with ethanol, and dry to obtain pretreated porous solid filler.

[0012] Preferably, the weight ratio of the porous solid filler to the chitosan is (4-6):1.

[0013] By adopting the above technical solutions, the breathability, hydrophilicity, and moisture-wicking properties of the breast patch are further improved. Placing the porous solid filler in a benzenesulfonic acid ethanol solution and heating it introduces sulfonic acid groups onto its surface, significantly enhancing the filler's hydrophilicity. This allows the breast patch to better absorb sweat from the skin, keeping the chest skin dry and comfortable, reducing discomfort such as itching and redness caused by stuffy sweat, making it especially suitable for prolonged wear. Chitosan is added in step 2. Chitosan itself has good hydrophilicity and hygroscopicity, further enhancing the filler's moisture-wicking ability. Simultaneously, the addition of chitosan also improves the filler's biocompatibility, making it safer and more comfortable to contact with human skin, reducing skin irritation.

[0014] In addition, the interaction between the treated porous solid filler and other components such as silicone oil is enhanced, making the overall adhesive distribution of the breast patch more uniform and stable, improving the adhesion between the breast patch and the skin, reducing the occurrence of edge curling, and thus enhancing the fixation effect of the breast patch.

[0015] Preferably, the foaming agent includes at least one of azodicarbonamide, azobisisobutyronitrile, and N,N'-dinitrospentamethylenetetramine.

[0016] By employing the above-mentioned technical solution, the foaming agent enables the formation of numerous microbubbles within the breast patch, reducing its overall density, making it lightweight, alleviating chest pressure, and improving wearing comfort, especially during prolonged wear without affecting normal breathing. Simultaneously, the microbubble structure increases the contact area between the breast patch and the skin, allowing it to better conform to the skin's curves, enhancing adhesion and providing a more even distribution, reducing edge curling, improving stability and fixation, and boosting confidence in wearing it. Furthermore, the microbubbles create breathable channels, enhancing breathability, reducing sweating and skin discomfort, keeping the skin dry, and improving the wearing experience.

[0017] Preferably, the desiccant is composed of calcium chloride and magnesium sulfate in a weight ratio of (2-3):1.

[0018] By employing the above technical solution, calcium chloride, with its strong hygroscopic properties, can efficiently absorb moisture from the skin surface, preventing stuffiness and keeping the skin dry and comfortable. Magnesium sulfate can absorb excess oil, preventing oily skin, and at the same time, it assists calcium chloride in improving moisture absorption efficiency. The synergistic effect of the two makes the chest patch have excellent moisture-wicking performance, especially when worn for a long time, it can continuously provide a cool environment for the chest skin and reduce discomfort such as itching and redness caused by moisture.

[0019] Preferably, the modified amino silicone oil is prepared by the following method: Epoxy silicone oil and fatty amine are mixed and reacted at 60-80℃ for 3-5 hours to obtain modified amino silicone oil, wherein the weight ratio of the epoxy silicone oil to the fatty amine is (0.5-1):1.

[0020] Preferably, the epoxy-based silicone oil is a terminal epoxy-based silicone oil with a molecular weight of 10,000-20,000.

[0021] By adopting the above technical solution and introducing fatty amine groups, the hydrophilicity of silicone oil is enhanced. This allows it to effectively improve the breathability and moisture absorption of the breast patch when combined with polyether-modified silicone oil to form a hydrophilic silicone oil, making it more comfortable to wear. The modified amino silicone oil makes the breast patch material softer, improving wearing comfort and flexibility, and reducing pressure on the skin. Simultaneously, the presence of amino groups enhances the adhesion between the silicone oil and the skin, as well as other components of the breast patch, making the overall structure of the breast patch more stable and reducing edge curling or loosening during use, ensuring a long-lasting and stable gathering and lifting effect. Furthermore, the modified amino silicone oil forms a smooth and soft film on the surface of the breast patch, improving its feel and making it smoother and more delicate, with no noticeable foreign body sensation when applied to the skin.

[0022] Preferably, the polyether-modified silicone oil is prepared by the following method: Allyl epoxy polyether and hydrogen-terminated silicone oil are added to a reactor, the temperature is raised to 75-85°C, an alkaline catalyst is added and stirring is started, the temperature is further raised to 105-110°C, and the reaction continues for 1-2 hours after the system becomes transparent to obtain polyether block silicone oil. The weight ratio of the allyl epoxy polyether to the hydrogen-terminated silicone oil is (0.5:1)-(1.5:1), and the amount of alkaline catalyst is 0.1-0.2% of the weight of the allyl epoxy polyether.

[0023] By employing the above technical solution, polyether-blocked silicone oil is formed by reacting allyl epoxy polyether and hydrogen-terminated silicone oil under specific conditions. This structure gives the silicone oil excellent flexibility. When used in breast pads, it allows the pads to better conform to the natural curves of the chest, reducing discomfort caused by material stiffness and improving wearing comfort. The polyether-blocked silicone oil gives the breast pads a soft and smooth feel. Compared to unmodified silicone oil, it reduces the stickiness of the breast pad surface, making the pads more delicate, smooth, and conforming better to the skin. The polyether structure can hold and transport moisture, thereby enhancing the moisture-wicking properties of the silicone oil. This helps keep the chest skin dry and reduces skin problems caused by sweating. The polyether-blocked silicone oil improves the adhesion between the breast pad and the skin, making the breast pad adhere more firmly to the skin, reducing the risk of displacement or falling off, and ensuring the stability and reliability of the breast pad during use.

[0024] Preferably, the molecular weight of the dual-terminated vinyl silicone oil is between 10,000 and 100,000, the vinyl content is 4-8%, and the viscosity is 30,000-50,000 cp.

[0025] By adopting the above-mentioned technical solutions, silicone oil has good rheological properties and film-forming properties, which can be evenly distributed in the breast patch to form a stable structure, which helps to improve the overall strength and flexibility of the breast patch, so that it fits the curve of the chest and maintains a certain degree of elasticity and durability.

[0026] Secondly, this application provides a method for preparing a skin-feel adhesive breast patch, using the following technical solution: A method for preparing a skin-feel adhesive breast patch includes the following preparation steps: S1. Mix the double-ended vinyl silicone oil, porous solid filler, hydrophilic silicone oil, hygroscopic agent, platinum catalyst, crosslinking agent and solvent evenly, then add foaming agent and mix evenly to obtain a mixture. S2. Coat the mixture into the mold and heat it to cure. The heating temperature is 110-120℃ to obtain the skin-feeling pressure-bonded breast patch.

[0027] By adopting the above technical solution In summary, this application has the following beneficial effects: 1. Excellent adhesion performance: Made primarily of double-end capped vinyl silicone oil and combined with an appropriate amount of crosslinking agent, it forms a unique colloidal structure that allows for close adhesion to the skin. It can be stably fixed to the chest without the need for shoulder straps, effectively solving the problem of fabric breast pads slipping off and meeting the usage needs when wearing strapless clothing such as tank tops and dresses.

[0028] 2. Excellent breathability: The introduction of porous solid filler creates breathable channels for the breast patch, allowing the chest skin to maintain good breathability. This effectively avoids discomfort such as stuffiness, itching, and redness caused by prolonged wear. Compared to silicone breast patches, it can keep the skin dry and comfortable during long-term use, improving the wearing experience. It is especially suitable for use in hot environments or long-term wearing scenarios.

[0029] 3. High comfort: The addition of hydrophilic silicone oil gives the breast pads skin-friendly properties, while the porous solid filler helps to reduce the overall weight of the breast pads and reduce the pressure on the chest. This makes it almost impossible for users to feel the presence of foreign objects during wear, allowing them to breathe freely and smoothly. This contrasts sharply with the heavy feel of silicone breast pads, giving users a comfortable feeling as if they are not wearing anything.

[0030] 4. Good durability: The use of organotin catalyst promotes the cross-linking reaction between raw materials, enabling the breast patch to form a stable chemical structure. Under normal use, it can maintain adhesion and shape stability for a long time and is not prone to problems such as curling or delamination. It can be repeatedly washed and reused. Detailed Implementation

[0031] Preparation Example Preparation Example 1 A modified amino silicone oil is prepared by the following method: 50g of epoxy silicone oil and 100g of fatty amine (n-hexylamine) were added to the reactor and mixed. The mixture was reacted at 60°C for 3 hours to obtain modified amino silicone oil. The weight ratio of epoxy silicone oil to fatty amine was 0.5:1.

[0032] Epoxy-terminated silicone oil is a type of silicone oil with terminal epoxy groups and a molecular weight of 10,000.

[0033] Preparation Example 2 A modified amino silicone oil is prepared by the following method: 80g of epoxy silicone oil and 100g of fatty amine (oleoamine) were added to the reactor and mixed. The mixture was reacted at 70°C for 4 hours to obtain modified amino silicone oil. The weight ratio of epoxy silicone oil to fatty amine was 0.8:1.

[0034] The epoxy-based silicone oil is a terminal epoxy-based silicone oil with a molecular weight of 15,000.

[0035] Preparation Example 3 A modified amino silicone oil is prepared by the following method: 100g of epoxy silicone oil and 100g of fatty amine (stearylamine) were added to the reactor and mixed. The mixture was reacted at 80°C for 5 hours to obtain modified amino silicone oil. The weight ratio of epoxy silicone oil to fatty amine was 1:1.

[0036] The epoxy-based silicone oil is a terminal epoxy-based silicone oil with a molecular weight of 20,000.

[0037] Preparation Example 4 Allyl epoxy polyether is an allyl epoxy polyoxyethylene polyether with an average molecular weight of 450, an epoxy value of 0.2 mol / 100g, and a double bond of 2.19 mmol / g.

[0038] The hydrogen-containing silicone oil was purchased from Ningbo Runhe High-Tech Materials Technology Co., Ltd., model number RH-H45.

[0039] A polyether-modified silicone oil is prepared by the following method: Add 50g of allyl epoxy polyether and 100g of hydrogen-terminated silicone oil to the reactor, heat to 75°C, add 0.5g of alkaline catalyst (potassium hydroxide) and start stirring, continue heating to 105°C, and continue the reaction for 1 hour after the system becomes transparent to obtain polyether block silicone oil.

[0040] The weight ratio of allyl epoxy polyether to hydrogen-terminated silicone oil is 0.5:1, and the amount of alkaline catalyst used is 0.1% of the weight of allyl epoxy polyether.

[0041] Preparation Example 5 A polyether-modified silicone oil is prepared by the following method: 100g of allyl epoxy polyether and 100g of hydrogen-terminated silicone oil were added to the reactor, the temperature was raised to 80°C, 1.5g of alkaline catalyst (sodium hydroxide) was added and stirring was started. The temperature was then raised to 108°C and the reaction was continued for 1.5h after the system became transparent to obtain polyether block silicone oil.

[0042] The weight ratio of allyl epoxy polyether to hydrogen-terminated silicone oil is 1:1, and the amount of alkaline catalyst used is 0.15% of the weight of allyl epoxy polyether.

[0043] Preparation Example 6 A polyether-modified silicone oil is prepared by the following method: Add 150g of allyl epoxy polyether and 100g of hydrogen-terminated silicone oil to the reactor, heat to 85°C, add 3g of alkaline catalyst (potassium hydroxide) and start stirring, continue heating to 110°C, and continue reaction for 2 hours after the system becomes transparent to obtain polyether block silicone oil.

[0044] The weight ratio of propyl epoxy polyether to hydrogen-terminated silicone oil is 1.5:1, and the amount of alkaline catalyst used is 0.2% of the weight of allyl epoxy polyether. Example

[0045] Example 1 A skin-feel adhesive breast patch is prepared by the following method: S1. Mix 300g of double-ended vinyl silicone oil, 400g of porous solid filler (porous silica), 60g of hydrophilic silicone oil, 50g of desiccant, 1g of platinum catalyst (chloroplatinic acid), 20g of crosslinking agent (hydrogen-containing silicone oil) and 800g of solvent (ethyl acetate) evenly, then add 8g of foaming agent (azodicarbonamide) and mix evenly to obtain a mixture. S2. Coat the mixture into the mold and heat it to cure at 110°C to obtain the skin-feeling pressure-bonded breast patch.

[0046] The hydrophilic silicone oil is composed of modified amino silicone oil from Preparation Example 1 and polyether modified silicone oil from Preparation Example 4 in a weight ratio of 1:2.

[0047] The desiccant is composed of calcium chloride and magnesium sulfate in a weight ratio of 2:1.

[0048] The molecular weight of the double-terminated vinyl silicone oil is 10,000, the vinyl content is 4%, and the viscosity is 30,000 cp.

[0049] The difference between Examples 2-3 and Example 1 lies in the types and amounts of raw materials used to prepare the skin-feel adhesive breast patch, as well as the experimental parameters. The specific differences are shown in Table 1. Table 1. Raw material types, dosages, and experimental parameters for preparing skin-feel adhesive breast patches. In Example 2, the hydrophilic silicone oil was composed of modified amino silicone oil from Preparation Example 2 and polyether modified silicone oil from Preparation Example 5 in a weight ratio of 1:3.

[0050] In Example 3, the hydrophilic silicone oil was composed of modified amino silicone oil from Preparation Example 3 and polyether modified silicone oil from Preparation Example 6 in a weight ratio of 1:4.

[0051] Example 4 A skin-feel adhesive breast patch, the difference between this embodiment and Embodiment 1 is that the porous solid filler is processed by the following method: 1) Soak 400g of porous solid packing in sodium hydroxide solution (mass fraction of 10%) for 1 hour to activate it and obtain activated porous solid packing; 2) The activated porous solid packing was added to a benzenesulfonic acid ethanol solution, heated to 50°C, and kept heated for 4 hours. Then, it was centrifuged, washed, and dried to obtain the sulfonated porous solid packing. The concentration of the benzenesulfonic acid ethanol solution was 0.4 mol / L. 3) Place 100g of chitosan in 800ml of 0.5mol / L acetic acid solution, heat to 70℃, and after the chitosan is completely dissolved, add sulfonated porous solid filler, cool to 55℃, maintain heating for 1.5h, filter, take the filter residue, wash with ethanol, and dry to obtain pretreated porous solid filler.

[0052] Example 5 A skin-feel adhesive breast patch, the difference between this embodiment and Embodiment 1 is that the porous solid filler is processed by the following method: 1) Soak 400g of porous solid packing in sodium hydroxide solution (mass fraction of 12%) for 2 hours to activate it and obtain activated porous solid packing; 2) The activated porous solid packing was added to a benzenesulfonic acid ethanol solution, heated to 60°C, and kept heated for 6 hours. Then, it was centrifuged, washed, and dried to obtain the sulfonated porous solid packing. The concentration of the benzenesulfonic acid ethanol solution was 0.8 mol / L. 3) Place 67g of chitosan in 1000ml of 0.8mol / L acetic acid solution, heat to 80℃, and after the chitosan is completely dissolved, add sulfonated porous solid filler, cool to 65℃, keep heating for 3h, filter, take the filter residue, wash with ethanol, and dry to obtain pretreated porous solid filler.

[0053] Example 6 A skin-feeling adhesive breast patch, the difference between this embodiment and embodiment 1 is that the hygroscopic agent is calcium chloride.

[0054] Comparative Example Comparative Example 1 A skin-feeling adhesive breast patch, the difference between this comparative example and Example 1 is that the hydrophilic silicone oil is a modified amino silicone oil from Preparation Example 1.

[0055] Comparative Example 2 A skin-feeling adhesive breast patch, the difference between this comparative example and Example 1 is that the hydrophilic silicone oil is the polyether-modified silicone oil from Preparation Example 4.

[0056] Comparative Example 3 A skin-feeling adhesive breast patch, the difference between this comparative example and Example 1 is that polyethylene glycol 200 is used instead of hydrophilic silicone oil.

[0057] Comparative Example 4 A skin-feeling adhesive breast patch, the difference between this comparative example and Example 1 is that sodium alginate is used instead of a moisture absorbent.

[0058] Comparative Example 5 A skin-feel adhesive breast patch, the difference between this comparative example and Example 1 is that silica is used instead of a foaming agent.

[0059] Detection methods / test methods Adhesion performance test: Purchase human silicone raw materials from Dongguan Xubai New Material Technology Co., Ltd., solidify the human silicone raw materials to form skin materials, and cut them into strips with a size of 25mm×100mm; The skin-feel adhesive breast patches prepared in Examples 1-6 and Comparative Examples 1-5 were all cut into strips with a size of 25mm × 100mm to obtain breast patch samples; Place the breast patch sample onto the surface of the simulated skin material, and gently roll it with a roller to remove air bubbles and make the adhesion tighter, ensuring that the adhesive area is flat and free of air bubbles.

[0060] Set the peel angle of the peel strength tester to 180° and the peel speed to 300 mm / min. Fix one end of the simulated skin material with the breast patch attached to the lower clamp of the peel strength tester, and fix the other end (the unattached part) to the upper clamp. Ensure that the clamp is firmly held and the sample is in a naturally straightened state before testing and calculating the average peel strength.

[0061] Repeated adhesion test: Each type of breast patch was repeatedly adhered 50 times, and the peel strength value was recorded after each adhesion.

[0062] Water washing test: Place the repeatedly pasted breast patch sample into a water washing machine and wash it according to the normal washing program (40℃ water temperature, normal washing mode) for 10 minutes. After washing, remove the breast patch and let it air dry or use a dryer to dry it. Record the appearance changes of the breast patch after drying (such as whether it curls or deforms).

[0063] Breathability: The skin-feeling adhesive breast patches prepared in Examples 1-6 and Comparative Examples 1-5 were all cut into samples with a size of 50mm×50mm. Using a YG(B)461E air permeability tester, the breast patch samples were fixed on the test hole of the air permeability tester, ensuring that the samples were flat and wrinkle-free. The pressure difference of the tester was set to 100Pa, and the amount of air passing through the sample was measured for 60 seconds.

[0064] Hygroscopicity: The skin-feeling adhesive breast patches prepared in Examples 1-6 and Comparative Examples 1-5 were all cut into samples with a size of 50mm×50mm. The breast patch samples were then pretreated in a dry environment for 24 hours, and the initial weight (m1) was measured. The breast patch samples were then placed in a constant temperature and humidity chamber for 2 hours to allow the samples to fully absorb moisture. After the samples were removed, the weight (m2) after moisture absorption was quickly measured under the same conditions. Each sample was repeated 3 times and the average value was taken to calculate the moisture absorption rate: Moisture absorption rate (%) = (m2-m1) / m1×100.

[0065] Softness Test: The skin-feel adhesive breast patches prepared in Examples 1-6 and Comparative Examples 1-5 were cut into uniform sizes of 10cm*10cm. Using a KES-FB softness tester, a pre-pressure of 1N was applied, and the probe was pressed downwards at a constant speed of 10mm / min, causing the sample to bend and deform. When the probe was pressed down to a certain depth of 3mm, the pressure was stopped, and the probe was slowly withdrawn. The force change during the withdrawal process was recorded. After the test, the average of three test results was taken as the bending stiffness value of the sample. The experimental data are shown in Table 2. Table 2. Experimental data of Examples 1-6 and Comparative Examples 1-5 As can be seen from the experimental data of Example 1 and Comparative Examples 1-5, the skin-feeling pressure-adhesive breast pad prepared by the formula in this application can firmly adhere to the skin, while improving the breathability and moisture absorption of the breast pad, reducing discomfort such as stuffiness and sweating of the chest skin. It is soft in texture and has good skin-friendliness, avoiding the discomfort caused by the hardness of silicone breast pad material. It can also withstand the test of long-term wear, reducing the decrease in adhesion and curling, and maintaining the fixation effect.

[0066] As can be seen from the experimental data of Examples 1 and 4-5, the porous inorganic filler treated by the method in this application further enhances the adhesion of the chest patch, makes the fixation effect more stable, and further improves the breathability and moisture absorption, providing users with a more comfortable wearing experience. It can more effectively reduce problems such as skin stuffiness and sweating, and has greater flexibility, further reducing the pressure on the chest.

[0067] The experimental data from Examples 1 and 6 show that using calcium chloride and magnesium sulfate together can improve the breathability and moisture absorption of the breast patch.

[0068] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A skin-feel adhesive breast patch, characterized in that, It is prepared from the following raw materials in parts by weight: 30-50 parts of double-ended vinyl silicone oil 40-60 parts of porous solid filler 6-9 parts of hydrophilic silicone oil 5-10 parts of desiccant 0.8-1.6 parts of foaming agent Platinum catalyst 0.1-0.3 parts 2-4 parts crosslinking agent 80-100 parts of solvent The hydrophilic silicone oil is composed of modified amino silicone oil and polyether modified silicone oil in a weight ratio of 1:(2-4).

2. The skin-feel adhesive breast patch according to claim 1, characterized in that: The porous solid packing is processed by the following method: 1) Soak the porous solid packing material in sodium hydroxide solution for 1-2 hours to activate it, thus obtaining activated porous solid packing material; 2) The activated porous solid packing is added to a benzenesulfonic acid ethanol solution, heated to 50-60℃, and kept heating for 4-6 hours. Then, it is centrifuged, washed, and dried to obtain sulfonated porous solid packing. The concentration of the benzenesulfonic acid ethanol solution is 0.4-0.8 mol / L. 3) Place chitosan in a 0.5-0.8 mol / L acetic acid solution, heat to 70-80℃, and after the chitosan is completely dissolved, add sulfonated porous solid filler, cool to 55-65℃, maintain heating for 1.5-3 hours, filter, take the filter residue, rinse with ethanol, and dry to obtain pretreated porous solid filler.

3. The skin-feel adhesive breast patch according to claim 2, characterized in that: The weight ratio of the porous solid filler to the chitosan is (4-6):

1.

4. The skin-feel adhesive breast patch according to claim 1, characterized in that: The foaming agent includes at least one of azodicarbonamide, azobisisobutyronitrile, and N,N'-dinitrospentamethylenetetramine.

5. The skin-feel adhesive breast patch according to claim 1, characterized in that: The desiccant is composed of calcium chloride and magnesium sulfate in a weight ratio of (2-3):

1.

6. The skin-feel adhesive breast patch according to claim 1, characterized in that, The modified amino silicone oil is prepared by the following method: Epoxy silicone oil and fatty amine are mixed and reacted at 60-80℃ for 3-5 hours to obtain modified amino silicone oil, wherein the weight ratio of the epoxy silicone oil to the fatty amine is (0.5-1):

1.

7. The skin-feel adhesive breast patch according to claim 1, characterized in that: The epoxy-based silicone oil is a terminal epoxy-based silicone oil with a molecular weight of 10,000-20,000.

8. The skin-feel adhesive breast patch according to claim 1, characterized in that: The polyether-modified silicone oil is prepared by the following method: Allyl epoxy polyether and hydrogen-terminated silicone oil are added to a reactor, the temperature is raised to 75-85°C, an alkaline catalyst is added and stirring is started, the temperature is further raised to 105-110°C, and the reaction continues for 1-2 hours after the system becomes transparent to obtain polyether block silicone oil. The weight ratio of the allyl epoxy polyether to the hydrogen-terminated silicone oil is (0.5:1)-(1.5:1), and the amount of alkaline catalyst is 0.1-0.2% of the weight of the allyl epoxy polyether.

9. The skin-feel adhesive breast patch according to claim 1, characterized in that: The dual-terminated vinyl silicone oil has a molecular weight of 10,000-100,000, a vinyl content of 4-8%, and a viscosity of 30,000-50,000 cp.

10. A method for preparing a skin-feel adhesive breast patch as described in any one of claims 1-9, characterized in that, The preparation steps include the following: S1. Mix the double-ended vinyl silicone oil, porous solid filler, hydrophilic silicone oil, hygroscopic agent, platinum catalyst, crosslinking agent and solvent evenly, then add foaming agent and mix evenly to obtain a mixture. S2. Coat the mixture into the mold and heat it to cure. The heating temperature is 110-120℃ to obtain the skin-feeling pressure-bonded breast patch.